2022
DOI: 10.1021/acs.jpcb.2c00303
|View full text |Cite
|
Sign up to set email alerts
|

Polaron Delocalization Dependence of the Conductivity and the Seebeck Coefficient in Doped Conjugated Polymers

Abstract: Conjugated polymers are promising materials for thermoelectrics as they offer good performances at near ambient temperatures. The current focus on polymer thermoelectric research mainly targets a higher power factor (PF; a product of the conductivity and square of the Seebeck coefficient) through improving the charge mobility. This is usually accomplished via structural modification in conjugated polymers using different processing techniques and doping. As a result, the structure−charge transport relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Ladder-type conjugated polymers (LCPs) are a promising class of conjugated polymers where the polymer backbone is composed of double-stranded fused-ring structure that limits its torsional rotation. Because of this, LCPs usually have highly rigid coplanar conformations that exhibit excellent mechanical properties, as well as thermal and chemical stability. Coplanar polymer backbones can extend intrachain delocalization that facilitate intrachain charge transfer and are also beneficial for strong π–π interactions that promote interchain charge transport. These unique advantages render ladder-type conjugated polymers as highly promising in organic electronic devices including organic thin film transistors (OTFTs), , organic electrochemical transistors (OECTs), , organic thermoelectrics (OTEs), lithium-/sodium-ion batteries (LIBs/SIBs), and supercapacitors. , However, the greatest challenge for LCPs synthesis and characterization is insolubility, either due to cross-linking or high molecular weight. The latter becomes an issue when the π-system in each repeating unit becomes too big.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ladder-type conjugated polymers (LCPs) are a promising class of conjugated polymers where the polymer backbone is composed of double-stranded fused-ring structure that limits its torsional rotation. Because of this, LCPs usually have highly rigid coplanar conformations that exhibit excellent mechanical properties, as well as thermal and chemical stability. Coplanar polymer backbones can extend intrachain delocalization that facilitate intrachain charge transfer and are also beneficial for strong π–π interactions that promote interchain charge transport. These unique advantages render ladder-type conjugated polymers as highly promising in organic electronic devices including organic thin film transistors (OTFTs), , organic electrochemical transistors (OECTs), , organic thermoelectrics (OTEs), lithium-/sodium-ion batteries (LIBs/SIBs), and supercapacitors. , However, the greatest challenge for LCPs synthesis and characterization is insolubility, either due to cross-linking or high molecular weight. The latter becomes an issue when the π-system in each repeating unit becomes too big.…”
mentioning
confidence: 99%
“…Such polaron delocalization is beneficial for charge transport and can be seen from the higher conductivity of Cl 2 –BAL as compared to Cl 4 –BAL. Polaron delocalization can also enhance the Seebeck coefficient through increasing the polaron’s vibrational entropy . The simultaneous enhancement in both conductivity and Seebeck coefficient through polaron delocalization is likely to be another reason for the more superior thermoelectric performance of Cl 2 –BAL as compared to Cl 4 –BAL.…”
mentioning
confidence: 99%
“…This trend agrees with several studies having reported that the improvement of the order of the polymeric chains induces an increase in the mobility of the charge carrier, which causes the simultaneous increase in the Seebeck coefficient and the electrical conductivity in the π-π stacking direction. [24][25][26][27] Therefore, the counterion used plays a fundamental role not only in the doping of the polymeric chains but also in the polymer chain conformation. Figure 5 shows a schematic representation of PEDOT polymeric chains ordering depending on the counterion used during the electrochemical synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…As the polaron delocalizes and spreads over more positions (larger counterion), the vibrational modes smooth out, and the total vibrational entropy change for the polaron associated with these atomic positions increases, improving the Seebeck coefficient. [ 27 ] Therefore, the use of BTFMSI as a counterion in the PEDOT showed the highest Power Factor since is the largest counterion used, allowing a greater delocalization of the polarons and an improvement in the ordering of the polymeric chains.…”
Section: Resultsmentioning
confidence: 99%
“…The small I ON /I OFF ratio of the proquinoidal structures of rNDI-NN/SS suggests the presence of excess charge carriers, which is consistent with their biradical characters observed in EPR measurement (Figure 2). 66 To evaluate the effect of dopants on the charge transport properties of rNDI-based polymers, different dopant concentrations within these four polymer films are applied for OFET performance optimization. 55 2.…”
Section: X-ray Photoelectron Spectra (Xps) and Ultraviolet Photoelect...mentioning
confidence: 99%